Transforming research and relationships through collaborative tribal-university partnerships on Manoomin (wild rice). Issue 115 (January 2021) - Matson, Laura; Ng, G.-H. Crystal; Dockry, Michael; Nyblade, Madeline; King, Hannah Jo; Bellcourt, Mark; Bloomquist, Jeremy; Bunting, Perry; Chapman, Eric; Dalbotten, Diana; Davenport, Mae A.; Diver, Karen; et al.
Highlights: Manoomin (wild rice) is a sacred food and relative for Great Lakes American Indians. University-tribal partnership transforms interdisciplinary research on manoomin. Ten tenets for responsible university research with Indigenous peoples. Collaborative research to support tribal sovereignty and environmental justice. Abstract: Manoomin, the Ojibwe word for wild rice, grows in shallow lakes and streams and provides physical, spiritual, and cultural sustenance as a sacred food and relative for Indigenous peoples across the Great Lakes region of North America. Unfortunately, Manoomin has been declining due to multiple environmental stressors. In 2018, an interdisciplinary group from the University of Minnesota came together with natural resource managers from tribes and inter-tribal organizations to understand Manoomin within its socio-environmental context. This partnership grew despite a history fraught with settler colonial structures of knowledge production and commodification. Based on lessons learned from building this transformational partnership, this paper describes ten tenets for responsible research: 1) Honor Indigenous sovereignty and rights; 2) Address past and present harms; 3) Be on the path together with researchers and Indigenous partners; 4) Recognize, respect, and value Indigenous participation and intellectual labor; 5) Encourage the robust exchange of ideas; 6) Recognize that documents formalizing a relationship are not the whole relationship; 7) Make a plan for identifying and protecting sensitive Indigenous data; 8) Be prepared to navigate institutional obstacles; 9) Seek, support, and collaborate with diverse students; and 10) Actively listen and be open to different ways of engaging with the world. These lessons can serve as tools to form accountable partnerships that enable robust, nuanced, and effective environmental science, policy, and stewardship.